معايير الاختيار للرهونات الإسلامية: دراسة حالة للعائلات البريطانية المسلمة - Tameme, Mohammed (مجلة العلوم الإدارية و الإقتصادية, 2016)
This paper investigates the choice criteria for the Islamic mortgages among the British Muslims who are seeking Islamic home financing. This research deems to establish a specific rank of choice criteria for Islamic Mortgages. Furthermore, these choice criteria will also be ranked according to the selected factors such as ethnicity and kind of tenures to find the main marketing implications. This study employed quantitative survey technique by using primary data collected from the Muslim Communities living in East London by self administered questionnaires and analyzed using frequencies, independent samples t-test and ANOVA test. The result suggest that “the deposit required by the bank” is the most important choice criteria and “the reputation of the bank” is the least important choice criteria. Moreover, there are no significant differences between renters and homeowners regarding the effects of the main criteria encouraging them to choose their Islamic home loan from different Islamic mortgage providers available in the market. The results of the survey are only applicable to the UK Muslims. The findings will be of interest to the Islamic mortgages providers to learn and plan attractive packages of Islamic mortgages that meet the British Muslims needs. Academically this study contributes to exiting literature of the UK experience of Islamic finance by providing an empirical study of choice criteria of Islamic mortgages which is not previously studied.